Christian Churches Converted into Mosques as Described in the Notes of Vasily Grigorovich-Barsky - Buzykina , Yulia N. (Actual Problems of Theory and History of Art, 2024)
The travel notes of Vasily Grigorovich-Barsky contain a number of descriptions of mosques that were previously Christian churches. The analysis of the text allows us to divide them into three groups. The first includes huge cathedrals that were converted into mosques with a greater or lesser degree of alteration to the original structure, with Christian access limited or prohibited. The second group also includes former Christian churches, access to which is open to Christians, including for the purpose of visiting sanctuaries and even holding liturgies. The third group includes mosques that Barsky only mentions without describing in detail. It can be concluded that in the Ottoman Empire in the first half of the 18th century, there was a dual attitude towards Christian churches that were rebuilt or transformed into mosques. Those that played an important role in the religious life of Muslims were sacredly guarded from infidels, while others, which were also important Christian holy sites, were available to believers in their original form. The purpose of Barsky’s listing of all such objects may have been an attempt to determine the real number of Christian shrines in the East, possibly with the far-reaching goal of returning them to the Christians.
Keywords: Grigorovich-Barsky; travel notes; pilgrimages; mosques; Christian archeology